Treatment Cost of Wilms Tumor in Bangladesh - Taher, Tania; Islam, Afiqul; Haroon, Kaisar; Urmy, Nushrat Jahan; Roshni, Naima (International Journal of Human and Health Sciences (IJHHS), 2026)
Wilms tumor is the most common primary malignant renal tumor of childhood. Treatment of Wilm’s tumor consists of surgery, chemotherapy and occasionally radiotherapy. Counseling of parents, regarding the treatment cost is one of the most important components of treatment. However, as there is no published article or data is available in Bangladesh regarding the actual treatment cost of the disease, it becomes very difficult for the paediatric oncologists and paediatricians to give exact idea to the parents about the treatment cost. This cross-sectional, observational study was aimed to ascertain the treatment cost of Wilms tumor in Bangladesh. The study was done in the Department of Paediatric Hematology & Oncology and Department of Paediatric Surgery of Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital and Department of Paediatric Surgery of Dhaka Shishu (Children) Hospital, Dhaka, Bangladesh, between December 2010 and May 2011. Sixteen patients were enrolled from indoor and outpatient department of both the hospitals. Data was collected by interviewing parents and checking the order for chemotherapy. Investigation cost and medicine cost was calculated from money receipt of the hospital and medicine store respectively. Data was noted in the prepared questionnaire form and cost of treatment of individual patient was calculated. The treatment cost including operative, chemotherapy and radiotherapy cost was calculated in free bed and paying bed of both the hospitals. In free bed, treatment cost for stage–I was USD 427.26, while for stage II–IV was USD 529.35. In paying bed, treatment cost was USD 548.59 for stage–I, USD 653.24 for Stage II–IV, and USD 2802.71 for relapsed cases with intensive chemotherapy. In private hospitals, treatment cost was USD 756.35 and USD 858.44, for stage–I and Stage II–IV respectively. To conclude, treatment cost depended upon the staging, histology and whether the treatment was done in Government Hospital or private hospital. However, if a child with Wilms tumor presents at earlier stage, the treatment is quite affordable at around USD 425 in government tertiary level hospital in Bangladesh. International Journal of Human and Health Sciences Vol. 10 No. 02 Apr’26 Page: 99-102